NATURE AND GENETIC STATUS RELATIONSHIP WITH THE FIRST MENSTRUATION (MENARCHE) ON STUDENTS OF SMP NEGERI 17 BANDA ACEH IN 2016 - A, Raudhatun Nuzul Z (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2017)
Menarche is an early sign of a womans entry in reproduction. Based on the results of basic health research in 2010 there were 5.2% of children in 17 Provinces in Indonesia have entered menarche age under 12 years old. Menarche can occur earlier by age 9-10 or later at the age of 17 years. Based on data obtained from SMP Negeri 17 Banda Aceh consists of 27 classes with a total of 372 female girls. there are almost all students who experience menarche at age> 12 years. This research aims to know the relationship between nutritional status and genetic with menstrual age first (menarche) at schoolgirl of SMP Negeri 17 Banda Aceh Year 2016. The type of research is analytic with cross-sectional approach conducted in SMP Negeri 17 Banda Aceh in June the number of samples in this study as many as 79 people with random sampling technique Data collection using questionnaires and statistical tests using correlation test. Based on the statistical test, the relationship of nutritional status with the age of the first menstrual period (Menarche) on the student, with the value of P value = 0,000 the genetic relationship with the first menstrual period (Menarche) at the student, with P value = 0,000. There is a relationship between nutritional status, genetics with the first menstrual period (Menarche) It is expected to increase students knowledge of the relationship between nutritional and genetic status with age of menarche.Keywords: Nutritional, Genetic and Menarche Status